Human rights approaches to suicide in prison: implications for policy, practice and research - Mary Rogan (BMC, 2018)
Abstract Background International human right standards place obligations on prison authorities to take reasonable steps to prevent suicides in prison and to investigate those which occur. Those human rights instruments contain minimum standards which states must abide by. Human rights principles can also be used in analysis of why suicides occur in prison. Methods This paper examines human rights standards on suicide and its prevention provided by the United Nations Standard Minimum Rules for the Treatment of Prisoners, the European Prison Rules, the work of the European Committee for the Prevention of Torture and Inhuman and Degrading Treatment or Punishment, and judgments of the European Court of Human Rights. Particular consideration is given to European human rights standards in light of the literature suggesting that European approaches tend to favour the promotion of human rights. A legal research methodology is employed. Results The paper examines key elements of human rights obligations in this field: the duty to pay particular attention to prisoners with particular mental health needs; duties to provide healthcare of an adequate standard; a duty on the prison authorities to ensure a proper information flow within prisons to identify risks; and particular duties to avoid using solitary confinement and to deploy safeguards when it is used. The paper also describes the obligations to investigate which arise after a suicide in prison: there must be an investigation instigated by the state which is independent, acts promptly and is open to public scrutiny, which is capable of giving rise to a finding of responsibility and is able to acquire relevant evidence, and which gives the next of kin of the deceased person an opportunity to participate. Conclusions All those responsible for preventing and responding to suicides in prison must fulfil these human rights obligations, and doing so would support a culture of protecting human rights in prison. In addition, compliance with the human rights standards described here should become a factor more regularly examined in analyses of why suicides occur in prison.